Do Foley Catheters Adequately Drain the Bladder? Evidence from CT Imaging Studies - Svetlana Avulova (International Brazilian Journal of Urology, 2015)
ABSTRACT Introduction: The Foley catheter has been widely assumed to be an effective means of draining the bladder. However, recent studies have brought into question its efficacy. The objective of our study is to further assess the adequacy of Foley catheter for complete drainage of the bladder. Materials and Methods: Consecutive catheterized patients were identified from a retrospective review of contrast enhanced and non-contrast enhanced computed tomo-graphic (CT) abdomen and pelvis studies completed from 7/1/2011-6/30/2012. Residual urine volume (RUV) was measured using 5mm axial CT sections as follows: The length (L) and width (W) of the bladder in the section with the greatest cross sectional area was combined with bladder height (H) as determined by multiplanar reformatted images in order to calculate RUV by applying the formula for the volume (V) of a sphere in a cube: V=(ϖ/6)*(L*W*H). Results: RUVs of 167 (mean age 67) consecutively catheterized men (n=72) and women (n=95) identified by CT abdomen and pelvis studies were calculated. The mean RUV was 13.2 mL (range: 0.0 mL-859.1 mL, standard deviation: 75.9 mL, margin of error at 95% confidence:11.6 mL). Four (2.4%) catheterized patients had RUVs of >50 mL, two of whom had an improperly placed catheter tip noted on their CT-reports. Conclusions: Previous studies have shown that up to 43% of catheterized patients had a RUV greater than 50 mL, suggesting inadequacy of bladder drainage via the Foley catheter. Our study indicated that the vast majority of patients with Foley catheters (97.6%), had adequately drained bladders with volumes of <50 mL.